Non-perturbative finite-temperature Yang-Mills theory - Cyrol, Anton Konrad; Pawlowski, Jan M.; Mitter, Mario; Strodthoff, Nils (Arxiv, 2017)
We present non-perturbative correlation functions in Landau-gauge Yang-Mills theory at finite temperature. The results are obtained from the functional renormalisation group within a self-consistent approximation scheme. In particular, we compute the magnetic and electric components of the gluon propagator, and the three- and four-gluon vertices. We also show the ghost propagator and the ghost-gluon vertex at finite temperature. Our results for the propagators are confronted with lattice simulations and our Debye mass is compared to hard thermal loop perturbation theory.
Last revised 17 Mar 2018
Gesehen am 06.11.2020